2021
DOI: 10.24843/ejmunud.2021.v10.i03.p01
|View full text |Cite
|
Sign up to set email alerts
|

Peran Stres Kerja Memediasi Pengaruh Beban Kerja Terhadap Burnout Perawat Rumah Sakit Daerah Mangusada Badung

Abstract: A person's condition when experiencing physical, mental, or emotional exhaustion is called burnout. This study aims to measure the level of burnout which is influenced by workload and is mediated by work stress. The research location is located at the Regional Hospital (RSD) Mangusada Badung, especially in the Oleg Room with a total sample of 50 nurses with the saturation sampling method. Data collection techniques using interview and dissemination systems. The type of data analysis used was path analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
12

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
1
3
0
12
Order By: Relevance
“…The results of this study are in accordance with research conducted by Jäppinen, et al (2021) which says that there is an influence between workload and work stress. The results of this study are also supported by previous research conducted by Dewi & Wibawa (2016), Tamping, et al (2021), Kurniawati, et al (2018), and Kusumawati & Dewi (2021 which stated that there was a positive and significant influence between workload and work stress.…”
Section: Hypothesis Testingsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of this study are in accordance with research conducted by Jäppinen, et al (2021) which says that there is an influence between workload and work stress. The results of this study are also supported by previous research conducted by Dewi & Wibawa (2016), Tamping, et al (2021), Kurniawati, et al (2018), and Kusumawati & Dewi (2021 which stated that there was a positive and significant influence between workload and work stress.…”
Section: Hypothesis Testingsupporting
confidence: 89%
“…In their research, Tamping, et al (2021) suggested that workload has a significant effect on work stress. This is supported by research (Kusumawati and Dewi, 2021), (Dewi and Wibawa, 2016) which also says that workload has a positive and significant effect on work stress.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…(2022) juga menunjukkan bahwa beban kerja memiliki pengaruh positif dan signifikan terhadap burnout di Badan Penyelenggara Jaminan Sosial Kota Padang. Selain itu, Kusumawati & Dewi (2021) menemukan bahwa burnout dipengaruhi secara positif dan signifikan oleh beban kerja pada perawat di Rumah Sakit Daerah Mangusada Badung. Penelitian oleh Ramli & Ahayalimudin (2023)juga menyatakan bahwa beban kerja berkontribusi terhadap burnout Berdasarkan temuan tersebut, dapat diajukan hipotesis sebagai berikut.…”
Section: Pendahuluanunclassified
“…Stres kerja merupakan kondisi seseorang yang mengalami perasaan tertekan secara fisik maupun psikologis yang mampu menghambat seseorang dalam menyelesaikan tanggung jawabnya (Kusumawati & Dewi, 2021). Beban kerja yang optimal dapat menurunkan stres kerja karyawan, begitu pula sebaliknya.…”
Section: Peran Stres Kerja Memediasi Beban Kerja Terhadap Semangat Ke...unclassified